Three-layer gradient self-healing hydrogel as well as preparation method and application thereof

By using three-layer gradient self-healing hydrogel prepared with chondroitin sulfate and carboxymethyl chitosan, the problem of lack of effective repair of articular cartilage in the prior art is solved, and the integrated repair of cartilage-bone tissue is achieved. It has strong self-healing and antioxidant properties.

CN119424764AActive Publication Date: 2025-02-14CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411399115.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-14
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

There is a lack of effective methods in the prior art to repair damaged articular cartilage, especially the integrated repair of cartilage and bone tissue.

Method used

Chondroitin sulfate/chitosan self-healing hydrogels were prepared by using chondroitin sulfate and carboxymethyl chitosan as raw materials, and tannin acid was introduced into the system to enhance self-healing The mechanical properties of the hydrogel impart adhesion and antioxidant properties, thereby preparing a three-layer gradient self-healing hydrogel similar to the natural cartilage tissue structure.

Benefits of technology

It has achieved integrated repair of cartilage-bone tissue, with super strong self-healing properties, excellent tissue adhesion and good antioxidant properties, and is suitable for the repair of articular cartilage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424764A_ABST
    Figure CN119424764A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to three-layer gradient self-healing hydrogel as well as a preparation method and application thereof. The invention provides a composition for preparing three-layer gradient self-healing hydrogel. The composition comprises a composition A, a composition B and / or a composition C, the composition A and the composition B are both composed of modified chondroitin sulfate, carboxymethyl chitosan and tannic acid, and the difference is that the concentration of tannic acid in the composition A is 0.5-1.5% w / v, and the concentration of tannic acid in the composition B is 2.5-3.5% w / v; the composition C is prepared from modified chondroitin sulfate, carboxymethyl chitosan, tannic acid and nano-hydroxyapatite, wherein the concentration of the tannic acid is 2.5 to 3.5 percent w / v. The three-layer gradient self-healing hydrogel has good self-healing performance, mechanical performance, tissue adhesion performance and oxidation resistance, and can be applied to integrated repair of articular cartilage-bone tissue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a three-layer gradient self-healing hydrogel and a preparation method and application thereof. Background Art

[0002] Articular cartilage is a layer of connective tissue covering the joint surface. The surface of normal cartilage is smooth and elastic, which can reduce the vibration and impact caused by movement. When the articular cartilage is damaged or degenerated, it will cause pain and limited movement. Because cartilage tissue has highly differentiated blood vessels, once the cartilage tissue is damaged, its self-repair ability is very limited. And damage to articular cartilage is often accompanied by integrated damage to the subchondral bone. Existing studies have shown that a single treatment strategy targeting articular cartilage is often limited in effect, and combining cartilage with subchondral bone for comprehensive treatment can achieve better therapeutic effects. Therefore, combining articular cartilage with bone tissue engineering to construct an integrated repair material for articular cartilage-bone tissue is of great significance for the integrated repair of cartilage-bone.

[0003] Hydrogels are very similar in structure to the extracellular matrix (ECM) of natural cartilage cells, have good biocompatibility and mechanical properties, and are the first choice for cartilage repair materials. Among them, self-healing hydrogels have become a research hotspot in the field of cartilage repair due to their excellent self-repair function. Self-healing hydrogels are a new type of hydrogel that can automatically restore its integrity and functionality without any external force after being damaged. Articular cartilage tissue has a three-layer gradient structure from top to bottom. Therefore, from the perspective of tissue engineering, it is expected to achieve cartilage repair by constructing a layered gradient self-healing hydrogel material with a structure similar to that of natural tissue.

[0004] In the prior art, patent CN103721293A reports a photo-crosslinked multilayer gradient hydrogel with controllable release of active factors and a preparation method. The gel structure is three layers, and the main components of each layer are modified gelatin and modified carboxymethyl chitosan. The preparation method includes: double bond modification of gelatin and carboxymethyl chitosan with glycidyl methacrylate; re-modification of double bond modified gelatin with heparin; three modified gelatin and modified carboxymethyl chitosan and crosslinker PEGDMA and photoinitiator I2959 are respectively prepared into three reaction solutions, and the three reaction solutions are continuously injected into the mold in sequence, and then photo-crosslinked to prepare a multilayer gradient hydrogel with controllable release of active factors for gradient distribution of articular cartilage tissue repair.

[0005] Currently, there is a lack of effective methods for repairing damaged articular cartilage in clinical practice. Therefore, it is necessary to prepare a layered gradient self-healing hydrogel material with a structure similar to that of natural tissue for integrated cartilage-bone repair. Summary of the invention

[0006] In view of this, the present invention proposes a three-layer gradient self-healing hydrogel for integrated repair of articular cartilage-bone and its composition, preparation method and application. The present invention uses carboxymethyl chitosan, which is soluble in water and contains a large number of amino groups, and chondroitin sulfate, the main component of cartilage tissue, as raw materials, and prepares chondroitin sulfate / chitosan self-healing hydrogel through dynamic Schiff base reaction, and introduces TA to enhance the mechanical properties of the self-healing hydrogel, giving it adhesion and antioxidant properties. At the same time, based on the layered gradient structure of natural cartilage-bone, a three-layer gradient self-healing hydrogel is prepared by optimizing the preparation conditions and adding hydroxyapatite that can promote bone formation. The present invention provides a basis for preparing a new self-repairable gradient self-healing hydrogel to repair cartilage-bone tissue.

[0007] One of the purposes of the present invention is to provide a composition for preparing a three-layer gradient self-healing hydrogel.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A composition for preparing a three-layer gradient self-healing hydrogel, the composition comprising composition A, composition B and / or composition C; the composition A comprises modified chondroitin sulfate, carboxymethyl chitosan and tannic acid, the concentration of tannic acid in the composition A is 0.5% w / v-1.5% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:5-1:7; the composition B comprises modified chondroitin sulfate, carboxymethyl chitosan and tannic acid, the concentration of tannic acid in the composition B is 2.5% w / v-3.5% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:5-1:7; the composition C comprises modified chondroitin sulfate, carboxymethyl chitosan, tannic acid and nano-hydroxyapatite, the concentration of tannic acid in the composition C is 2.5% w / v-3.5% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:5-1:7.

[0010] Furthermore, in the composition A, the composition B and the composition C, the concentration of modified chondroitin sulfate is 18% w / v to 22% w / v; in the composition A, the composition B and the composition C, the concentration of carboxymethyl chitosan is 3% w / v to 5% w / v; and in the composition C, the concentration of nano-hydroxyapatite is 5% w / v to 7% w / v.

[0011] Furthermore, the modified chondroitin sulfate is aldehyde-modified chondroitin sulfate, wherein the aldehyde content is 1.0 mmol / g to 1.5 mmol / g.

[0012] Furthermore, the tannic acid concentration in the composition A is 1% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:6; the tannic acid concentration in the composition B is 3% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:6; the tannic acid concentration in the composition C is 3%, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:6; the modified chondroitin sulfate is aldehyde-modified chondroitin sulfate with a concentration of 20% w / v, wherein the aldehyde content is 1.2 mmol / g; the concentration of the carboxymethyl chitosan is 4% w / v; and the concentration of the nano-hydroxyapatite is 6% w / v.

[0013] A second object of the present invention is to provide a method for preparing the aforementioned three-layer gradient self-healing hydrogel.

[0014] To achieve the above object, the present invention adopts the following technical solutions:

[0015] The preparation method of the aforementioned three-layer gradient self-healing hydrogel comprises the following steps:

[0016] (1) Preparation of OCS1-CMCS-TA1 hydrogel: a modified chondroitin sulfate solution and a carboxymethyl chitosan solution are mixed to prepare a chondroitin sulfate / chitosan self-healing hydrogel through a dynamic Schiff base reaction; the chondroitin sulfate / chitosan self-healing hydrogel is immersed in a tannic acid solution with a concentration of 0.5% w / v to 1.5% w / v to obtain the OCS1-CMCS-TA1 hydrogel;

[0017] (2) Preparation of OCS1-CMCS-TA3 hydrogel: a modified chondroitin sulfate solution and a carboxymethyl chitosan solution were mixed to prepare a chondroitin sulfate / chitosan self-healing hydrogel through a dynamic Schiff base reaction; the chondroitin sulfate / chitosan self-healing hydrogel was immersed in a tannic acid solution with a concentration of 2.5% w / v to 3.5% w / v to obtain the OCS1-CMCS-TA3 hydrogel;

[0018] (3) Preparation of OCS1-CMCS / HAp6-TA3 hydrogel: adding nanohydroxyapatite to a carboxymethyl chitosan solution to obtain a CMCS / HAp solution; mixing the CMCS / HAp solution with a modified chondroitin sulfate solution to obtain an OCS1-CMCS / HAp6 hydrogel; soaking the OCS1-CMCS / HAp6 hydrogel in a tannic acid solution with a concentration of 2.5% w / v to 3.5% w / v to obtain the OCS1-CMCS / HAp6-TA3 hydrogel;

[0019] (4) Preparation of three-layer gradient self-healing hydrogel: stack the OCS1-CMCS-TA1 hydrogel obtained in step (1), the OCS1-CMCS-TA3 hydrogel obtained in step (2), and the OCS1-CMCS / HAp6-TA3 hydrogel obtained in step (3) in sequence from top to bottom to obtain the three-layer gradient self-healing hydrogel.

[0020] Furthermore, in step (1), the concentration of the tannic acid solution is 1% w / v; in steps (2) and (3), the concentration of the tannic acid solution is 3% w / v.

[0021] Furthermore, in steps (1) to (3), the concentration of the modified chondroitin sulfate solution is 20% w / v.

[0022] Furthermore, in steps (1) to (3), the concentration of the carboxymethyl chitosan solution is 4% w / v.

[0023] Furthermore, in steps (1) to (3), the volume ratio of the modified chondroitin sulfate solution to the carboxymethyl chitosan solution is 1:6.

[0024] Furthermore, in step (3), the concentration of the nano-hydroxyapatite is 6% w / v.

[0025] Furthermore, the preparation solvents of the modified chondroitin sulfate solution, the carboxymethyl chitosan solution and the tannic acid solution are all ultrapure water.

[0026] Furthermore, in steps (1) to (3), the hydrogel is immersed in the tannic acid solution for 30 minutes.

[0027] Furthermore, after the immersion is completed, the excess tannic acid solution on the surface of the hydrogel is rinsed with ultrapure water.

[0028] Furthermore, the aldehyde content of the modified chondroitin sulfate is 1.0 mmol / g to 1.5 mmol / g; the modified chondroitin sulfate is prepared by the following method: after dissolving chondroitin sodium sulfate salt, sodium periodate is added for oxidation reaction; after the reaction is completed, ethanol solution is added and stirred, and the obtained product is precipitated, dialyzed, and freeze-dried to obtain aldehyde-modified chondroitin sulfate.

[0029] Preferably, the oxidation reaction time is 6 hours.

[0030] Preferably, the precipitation is carried out at 4°C for 4 hours.

[0031] Preferably, the dialysis time is 3 days.

[0032] Most preferably, the modified chondroitin sulfate is prepared by the following method:

[0033] After dissolving the sodium sulfate salt of chondroitin, sodium periodate was added to react for 6 hours; then, an ethanol solution was added and stirred in the dark for 15 minutes, and the precipitated OCS was collected at 4°C for 4 hours. The precipitate was dialyzed with a MWCO300 dialysis bag for 3 days and freeze-dried to obtain aldehyde-modified chondroitin sulfate; the aldehyde content of the aldehyde-modified chondroitin sulfate was 1.2 mmol / g.

[0034] Furthermore, in step (4), the three-layer gradient self-healing hydrogel is prepared by utilizing the self-healing and adhesion properties of OCS1-CMCS-TA1 hydrogel, OCS1-CMCS-TA3 hydrogel and OCS1-CMCS / HAp6-TA3 hydrogel.

[0035] The third object of the present invention is to provide a three-layer gradient self-healing hydrogel prepared by the above-mentioned preparation method.

[0036] To achieve the above object, the present invention adopts the following technical solutions:

[0037] The three-layer gradient self-healing hydrogel is prepared by the above-mentioned preparation method.

[0038] Furthermore, the OCS1-CMCS-TA1 hydrogel, OCS1-CMCS-TA3 hydrogel and OCS1-CMCS / HAp6-TA3 hydrogel in the three-layer gradient self-healing hydrogel all have a double network structure, and the aldehyde group of the modified chondroitin sulfate reacts with the amino group of carboxymethyl chitosan to form a Schiff base, which constitutes the first cross-linked network structure of the hydrogel; the hydrogen bonds of tannic acid itself, and the hydrogen bonds formed between tannic acid and modified chondroitin sulfate and carboxymethyl chitosan, constitute the second cross-linked network structure of the hydrogel.

[0039] A fourth object of the present invention is to provide an application of the aforementioned composition and / or the aforementioned three-layer gradient self-healing hydrogel in the preparation of an integrated articular cartilage-bone tissue repair product.

[0040] The beneficial effects of the present invention are:

[0041] 1. The present invention uses chondroitin sulfate and carboxymethyl chitosan as raw materials, prepares chondroitin sulfate / chitosan self-healing hydrogel through dynamic Schiff base reaction between the two, and introduces tannic acid into the system to enhance the mechanical properties of the self-healing hydrogel, giving it adhesion and antioxidant properties. At the same time, from the perspective of bionics, by changing the preparation conditions and adding hydroxyapatite that can promote bone formation, a three-layer gradient self-healing hydrogel material similar to the structure of natural cartilage tissue is prepared, which is of great significance for the integrated repair of articular cartilage-bone tissue.

[0042] 2. The present invention provides a method for preparing a three-layer gradient self-healing hydrogel, explores the influence of the concentration and ratio of each raw material and different tannic acid concentrations on the mechanical, adhesion, antioxidant and other properties of the self-healing hydrogel, and finally obtains the optimal preparation conditions: the first layer: OCS1-CMCS-TA1 hydrogel, OCS1:CMCS=1:6, TA concentration is 1% w / v, OCS1 concentration is 20% w / v, and CMCS concentration is 4% w / v; the second layer is OCS1-CMCS-TA3 hydrogel, OCS1:CMCS=1:6, TA concentration is 3% w / v, OCS1 concentration is 20% w / v, and CMCS concentration is 4% w / v; the third layer is OCS1-CMCS / HAp-TA3 hydrogel, OCS1:CMCS=1:6, TA concentration is 3% w / v, HAp concentration is 6% w / v, OCS1 concentration is 20% w / v, and CMCS concentration is 4% w / v. The preparation method provided by the present invention adopts Schiff base reaction, the conditions are simple and mild, and the hydrogel material with self-repairing function can be prepared without external stimulation. The present invention provides a basis for preparing a new self-repairing gradient self-healing hydrogel to repair cartilage-bone tissue.

[0043] 3. The three-layer gradient self-healing hydrogel of the present invention has super strong self-healing performance. When two hydrogels are superimposed, the gaps in the hydrogels disappear after 1 hour, the hydrogels are completely self-healed after 3 hours, and the self-healing gaps are completely invisible after 5 hours and the color is uniform.

[0044] 4. The three-layer gradient self-healing hydrogel of the present invention has excellent tissue adhesion. The elastic moduli of the first to third layers of hydrogel are 282 KPa, 328 KPa, and 411 KPa, respectively, and the adhesion strengths are 5.7 KPa, 9.3 KPa, and 9.1 KPa, respectively.

[0045] 5. The three-layer gradient self-healing hydrogel of the present invention has excellent swelling properties. After absorbing water for 4 hours, the swelling rates of the first to third layers of the hydrogel are 1083%, 1077% and 954%, respectively.

[0046] 6. The three-layer gradient self-healing hydrogel of the present invention has excellent antioxidant properties. The DPPH removal rate of the first layer OCS-CMCS-TA1 hydrogel is 68%, the DPPH removal rate of the second layer OCS-CMCS-TA3 hydrogel is 81%, and the DPPH removal rate of the third layer OCS-CMCS / HAp-TA3 hydrogel is 80%. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the H NMR spectrum of chondroitin sulfate aldehyde modification;

[0048] Figure 2The gelation diagram of OCS1-CMCS-TA self-healing hydrogel and OCS1-CMCS / HAp-TA self-healing hydrogel;

[0049] Figure 3 The stress-strain curve of OCS1-CMCS single network self-healing hydrogel;

[0050] Figure 4 Elastic modulus diagram of OCS1-CMCS single network self-healing hydrogel;

[0051] Figure 5 The stress-strain curve of OCS2-CMCS single network self-healing hydrogel;

[0052] Figure 6 Elastic modulus diagram of OCS2-CMCS single network self-healing hydrogel;

[0053] Figure 7 The stress-strain curves of OCS1-CMCS-TA double network self-healing hydrogels with different TA concentrations;

[0054] Figure 8 Elastic modulus diagram of OCS1-CMCS-TA double network self-healing hydrogel with different TA concentrations;

[0055] Fig. 9 The stress-strain curves of OCS1-CMCS / HAp-TA double network self-healing hydrogels loaded with different HAp amounts;

[0056] Fig.10 The elastic modulus diagram of OCS1-CMCS / HAp-TA double network self-healing hydrogel loaded with different HAp amounts;

[0057] Fig.11 Schematic diagram of adhesion test;

[0058] Fig.12 The figure shows the adhesion performance test results of OCS-CMCS-TA double network self-healing hydrogel; Fig.12 -A and Fig.12 -B is a diagram showing the hydrogel adhering to a plastic glove and bearing a certain tensile force; Fig.12 -C is a diagram showing the hydrogel adhering to the skin; Fig.12 -D is a diagram showing the hydrogel adhering to the rubber; Fig.12 -E is a diagram showing the hydrogel adhering to the plastic tube; Fig.12 -F is a diagram showing the hydrogel adhering to a plastic glove;

[0059] Fig.13 Force-displacement curves of OCS-CMCS-TA hydrogels with different TA concentrations;

[0060] Fig.14 is the adhesion strength diagram of OCS-CMCS-TA hydrogels with different TA concentrations;

[0061] Fig.15 It is the force displacement curve of OCS1-CMCS / HAp-TA3 hydrogel loaded with hydroxyapatite nanoparticles;

[0062] Fig.16 is the adhesion strength diagram of OCS1-CMCS / HAp-TA3 hydrogel loaded with hydroxyapatite nanoparticles;

[0063] Fig.17 Schematic diagram of gradient self-healing hydrogel;

[0064] Fig.18 This is the SEM image of the hydrogel after freeze-drying, where: Fig.18 -A is the SEM image of OCS1-CMCS-TA1 hydrogel at a magnification of ×100; Fig.18 -B is the SEM image of OCS1-CMCS-TA3 hydrogel at a magnification of ×100; Fig.18 -C is the SEM image of OCS1-CMCS / HAp-TA3 hydrogel at a magnification of ×100; Fig.18 -D is the SEM image of OCS1-CMCS / HAp-TA3 hydrogel at a magnification of ×2000;

[0065] Fig.19 is a graph of the swelling ratio of OCS-CMCS-TA1, OCS-CMCS-TA3, and OCS-CMCS / HAp-TA3 hydrogels;

[0066] Fig. 20 is a diagram of the self-healing behavior of the hydrogel, where Fig. 20 -A is a microscopic observation of the self-healing behavior of the hydrogel. Fig. 20 -B is a macroscopic view of the self-healing behavior of the hydrogel;

[0067] Fig.21 is a graph showing the absorbance changes of different hydrogels after reacting with DPPH;

[0068] Fig. 22 Statistical graph of DPPH scavenging rate of different hydrogels. DETAILED DESCRIPTION

[0069] The technical solution of the present invention will be further described clearly and completely in conjunction with specific embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0070] In the present invention, chondroitin sulfate (CS) is a sulfonated glycosaminoglycan composed of alternating units of β-1,4-linked glucuronic acid and β-1,3-N-acetyl-D-glucosamine. Chondroitin sulfate is distributed on the surface of almost all cells and is the main component of the extracellular matrix. It plays an important role in regulating cell migration, receptor binding and other cell functions. In addition to having biological activities such as anti-inflammatory, anti-tumor, and promoting cell regeneration, chondroitin sulfate is also widely used in biological scaffolds to participate in bone, cartilage, skin and other tissue engineering fields.

[0071] In the present invention, chitosan (CS) is a kind of mucopolysaccharide widely existing in nature, and is also a potential material for cartilage repair. As a product of chitin, chitosan is non-toxic, degradable, and has good adhesion. A large number of positively charged free amino groups in chitosan molecules can react with multivalent anions to form hydrogels, and then be used in the fields of biology, medicine, and food. In addition, chitosan is also the main component of connective tissue, and has characteristics such as anti-inflammatory and antibacterial effects and antioxidant properties. Carboxymethyl chitosan (CMCS) is a derivative of chitosan, which is prepared by introducing carboxymethyl functional groups into chitosan molecules. Carboxymethyl chitosan not only maintains the biocompatibility and biodegradability of chitosan, but also has better water solubility, film-forming property, moisture retention, antibacterial property and heavy metal chelation due to the introduction of carboxymethyl. Therefore, carboxymethyl chitosan is widely used in the field of medicine.

[0072] In the present invention, tannic acid (TA) is a natural polyphenol compound, rich in pyrogallol and catechol, and has multiple interactions. Existing studies have shown that TA can be used as a universal gelling agent to crosslink polymers into hydrogels; at the same time, tannic acid can also be used as a crosslinking agent for the modification of biomaterials. And tannic acid has strong antioxidant properties, because tannic acid is rich in pyrogallol and catechol, and pyrogallol hydroxyl and catechol hydroxyl can effectively remove oxygen free radicals, thereby blocking the continuous reaction of free radicals. The antioxidant property of tannic acid is mainly reflected in two aspects: 1) tannic acid can reduce the oxygen content in the environment through reduction reaction; 2) tannic acid can be used as a hydrogen donor, by releasing hydrogen to combine with free radicals in the environment, preventing the chain reaction caused by free radicals, thereby preventing the continuation and transmission of the oxidation process.

[0073] In the embodiments of the present invention, the main experimental instruments are shown in Table 1.

[0074] Table 1. List of experimental instruments

[0075] Device Name Device Model use Ultrasonic Cleaner SB-5200DTDN dispersion UV spectrophotometer UV755B analyze Constant temperature heating magnetic stirrer DF-101S Stirring Electric constant temperature drying oven DGG-9076A dry Freeze Dryer Lab-1D-80 Freeze drying Mechanical testing machine Sansi Taijie Measurement Scanning electron microscopy DX-7000 analyze

[0076] In the examples of the present invention, the main experimental raw materials are shown in Table 2.

[0077] Table 2. List of experimental raw materials

[0078]

[0079]

[0080] Example 1

[0081] (1) Chondroitin sulfate modification

[0082] Dissolve 1 g of chondroitin sodium sulfate in 20 mL of ultrapure water. After fully dissolved, add 1.5 g and 0.7 g of sodium periodate respectively, react for 6 h, then add 40 mL of ethanol solution and continue stirring for 15 min (protect from light). Collect the precipitated OCS at 4 ° C for 4 h, dialyze the precipitate with a MWCO300 dialysis bag for 3 days, and then lyophilize to obtain modified chondroitin sulfate, named OCS1 and OCS2 respectively.

[0083] (2) Preparation of single-network OCS-CMCS self-healing hydrogel

[0084] 1) Weigh 2 g of OCS1 and 2 g of OCS2 and dissolve them in 10 mL of ultrapure water to prepare 20% w / v OCS1 and OCS2 solutions, respectively.

[0085] 2) Weigh 0.4 g of carboxymethyl chitosan and dissolve it in 10 mL of ultrapure water. Stir for 1 h to form a transparent and uniform solution to obtain a 4% w / v CMCS solution.

[0086] 3) According to the test groups shown in Table 3, the OCS solution obtained in step 1) and the CMCS solution obtained in step 2) were mixed in a syringe at a certain volume ratio and placed at room temperature to form an OCS-CMCS single network hydrogel.

[0087] Table 3. Experimental grouping of single network OCS-CMCS self-healing hydrogels

[0088] Sample No. Proportion 1 OCS1:CMCS=1:4 2 OCS1:CMCS=1:6 3 OCS1:CMCS=1:8 4 OCS2:CMCS=1:4 5 OCS2:CMCS=1:6 6 OCS2:CMCS=1:8

[0089] (3) Preparation of double network OCS1-CMCS-TA self-healing hydrogel

[0090] 1) Weigh 2 g of OCS1 and dissolve it in 10 mL of ultrapure water to prepare a 20% w / v OCS1 solution.

[0091] 2) Weigh 0.4 g of carboxymethyl chitosan and dissolve it in 10 mL of ultrapure water. Stir for 1 h to form a transparent uniform solution to obtain a 4% w / v CMCS solution.

[0092] 3) The OCS1 solution obtained in step 1) and the CMCS solution obtained in step 2) are mixed in a syringe at a volume ratio of 1:6, and placed at room temperature to form an OCS-CMCS single network wet hydrogel; and a dry hydrogel is obtained after freeze-drying.

[0093] 4) Weigh 0.1 g, 0.3 g, 0.5 g and 1 g of tannic acid powder respectively and dissolve them in 10 mL of ultrapure water, and stir for 10 min to form 1% w / v, 3% w / v, 5% w / v and 10% w / v transparent uniform solutions.

[0094] 5) This experiment was divided into 4 groups, as shown in Table 4. The wet hydrogel prepared in step 3) and the freeze-dried dry hydrogel were immersed in 5 mL of TA solution of different concentrations for 30 min, and the excess TA solution on the surface of the hydrogel was washed with ultrapure water after immersion. The volume of the hydrogel was 4×10 -6 m 3 . A double network OCS1-CMCS-TA self-healing hydrogel was obtained.

[0095] Table 4. Experimental grouping table of double network OCS1-CMCS-TA self-healing hydrogel

[0096] Sample No. Proportion 7 OCS1:CMCS-TA1 8 OCS1:CMCS-TA3 9 OCS1:CMCS-TA5 10 OCS1:CMCS-TA10

[0097] (4) Preparation of double network OCS1-CMCS / HAp-TA self-healing hydrogel

[0098] 1) Weigh 2 g of OCS1 and dissolve it in 10 mL of ultrapure water to prepare a 20% w / v OCS1 solution.

[0099] 2) Weigh 0.4 g of carboxymethyl chitosan and dissolve it in 10 mL of ultrapure water. Stir for 1 h to form a transparent uniform solution. Then add 0.2 g, 0.4 g, 0.6 g, 0.8 g and 1.0 g of nanohydroxyapatite (HAp) respectively and stir magnetically for 30 min to fully mix HAp in the solution to form a milky white, transparent and uniform CMCS / HAp solution.

[0100] 3) The OCS1 solution obtained in step 1) and the CMCS / HAp solution obtained in step 2) were mixed in a syringe at a volume ratio of 1:6, and placed at room temperature to form OCS-CMCS / HAp single network hydrogels containing different amounts of HAp.

[0101] 4) Weigh 0.3 g of tannic acid powder and dissolve it in 10 mL of deionized water. After magnetic stirring for 10 min, a 3% w / v transparent uniform solution is formed.

[0102] 5) The OCS-CMCS / HAp wet hydrogels containing different amounts of HAp prepared in the above step 3) were respectively immersed in the 3% w / v TA solution prepared in the above step 4). After the immersion was completed, the excess TA solution on the surface of the hydrogel was rinsed with ultrapure water to obtain a double-network OCS1-CMCS / HAp-TA self-healing hydrogel.

[0103] Table 5. Experimental grouping table of double network OCS1-CMCS / HAp-TA self-healing hydrogel

[0104] Sample No. Proportion 11 OCS1:CMCS / HAp2-TA3 12 OCS1:CMCS / HAp4-TA3 13 OCS1:CMCS / HAp6-TA3 14 OCS1:CMCS / HAp8-TA3 15 OCS1:CMCS / HAp10-TA3

[0105] (5) Preparation of gradient self-healing hydrogel

[0106] The gradient self-healing hydrogel is prepared by utilizing the self-healing and adhesion properties of OCS1-CMCS-TA self-healing hydrogel and OCS1-CMCS / HAp-TA self-healing hydrogel. Among them, the first layer uses OCS1-CMCS-TA1 hydrogel, the second layer uses OCS1-CMCS-TA3 hydrogel, and the third layer uses OCS1-CMCS / HAp6-TA3 hydrogel. The prepared OCS1-CMCS-T1A hydrogel, OCS1-CMCS-TA3 hydrogel, and OCS1-CMCS / HAp6-TA3 hydrogel are stacked together from top to bottom to obtain the gradient self-healing hydrogel.

[0107] Example 2. Characterization of Chondroitin Sulfate Modification

[0108] (1) Nuclear magnetic resonance hydrogen spectrum test

[0109] H NMR ( 1 H NMR) shows different absorption peaks and chemical shifts by testing the different chemical environments of hydrogen atoms in molecules. The size of the chemical shift can be used to qualitatively analyze whether the modification of chondroitin sulfate is successful. 0.8g of the modified OCS is fully dissolved in 500μL of deuterated water and injected into the nuclear magnetic tube for nuclear magnetic test to verify whether it is successfully modified.

[0110] Results: The aldehyde modification of OCS was obtained by oxidation of the hydroxyl (-OH) on the CS main chain with sodium periodate. 1 H NMR Figure 1 As shown, the NMR of OCS is compared with that of CS. 1A new C=O characteristic peak appeared at 5.18 ppm in H NMR, indicating that the aldehyde group modification of CS was successful.

[0111] (2) Chondroitin sulfate aldehyde modification degree test

[0112] The aldehyde content of modified chondroitin sulfate was determined by hydroxylamine hydrochloride titration method. The specific experimental steps include: 1) Preparation of hydroxylamine hydrochloride-methyl orange solution: weigh 4.35g of hydroxylamine hydrochloride, dissolve it with a small amount of deionized water, add 1.5mL of 0.05% methyl orange aqueous solution, and dilute to 500mL for use. 2) Determination of aldehyde group of chondroitin sulfate: weigh 0.02g of OCS, and record the mass as m; add OCS to 5mL of hydroxylamine hydrochloride-methyl orange solution to dissolve, and let it stand for 3h for use. Titrate with 0.01mol / L sodium hydroxide solution until the red color changes to yellow, and record the volume as V1; and make a blank control, and record the volume as V0. Calculate the aldehyde content according to the following formula:

[0113] Aldehyde content (mmol / g) = (V1-V0) × n NaOH / 2W

[0114] Where V1 is the volume of sodium hydroxide consumed by the sample, V0 is the volume of sodium hydroxide consumed by the blank solution, and n NaOH is the molar concentration of sodium hydroxide solution (mol / L), W is the mass of OCS (g). Each group of experiments was performed three times in parallel and the average value was taken.

[0115] Results: The average volume of NaOH consumed by the blank group, OCS1 and OCS2, and the aldehyde content of OCS in the experiment are shown in Table 6. Hydroxylamine hydrochloride can react with aldehyde groups to form oximes and release HCl at the same time. The aldehyde content was calculated by titrating the amount of HCl and according to the above formula: the aldehyde content of OCS1 with 1.5g sodium periodate added was 1.2mmol / g, and the aldehyde content of OCS2 with 0.7g sodium periodate added was 0.875mmol / g.

[0116] Table 6. OCS aldehyde content

[0117] sample Average NaOH consumption (mL) Aldehyde content (mmol / g) Blank Group 4.2 / OCS1 9 1.2 OCS2 7.7 0.875

[0118] (3) Gelation

[0119] The specific gel formation of OCS1-CMCS-TA self-healing hydrogel and OCS1-CMCS / HAp-TA self-healing hydrogel is as follows: Figure 2As shown. In the process of forming OCS-CMCS-TA self-healing hydrogel, the aldehyde group of OCS1 reacts with the amino group of CMCS to form a Schiff base. This strong interaction constitutes the first cross-linked network structure of the hydrogel. However, the mechanical properties and adhesion properties of the prepared single network self-healing hydrogel are weak. For this reason, TA is introduced to solve this problem. TA's own hydrogen bonds and the hydrogen bonds formed with other TA components constitute the second cross-linked network structure of the hydrogel. The hydrogen bonds not only improve the mechanical properties but also improve the self-healing properties of the material. At the same time, TA's catechol can give the material adhesion and antioxidant properties, and hydroxyapatite can promote cartilage-bone formation.

[0120] Example 3. Mechanical properties test

[0121] The hydrogels No. 1-15 in Example 1 were made into cylindrical samples with a diameter of 1 cm and a height of 6 mm. The hydrogel compression test was carried out using a mechanical tester at a mode of 5 mm / min. The machine was stopped at the moment the gel was crushed. The elastic modulus of the hydrogel was obtained by calculating the slope of the straight line portion of the stress-strain curve. Three parallel samples were made for each group of experiments and the average value was taken.

[0122] The calculation formula of stress is as follows:

[0123] Stress = load / π×r 2 ×1000

[0124] Among them, load is the load value, unit is N.

[0125] The strain is calculated as follows:

[0126] Strain = position / h × 100

[0127] Among them, position is displacement, unit is mm.

[0128] The test results and analysis are as follows:

[0129] 1) Mechanics of single network OCS-CMCS self-healing hydrogels: Stress-strain curves and elastic modulus of single network self-healing hydrogels under different preparation conditions are shown in Figure 2. Figure 3 to Figure 6 As shown. Among them, Figure 3-4 OCS1-CMCS single network self-healing hydrogels with different ratios formed by highly modified OCS1 and CMCS can be seen under the same gelation environment that the elastic modulus reaches 93KPa when OCS1:CMCS=1:6, while the elastic modulus is lower than that of OCS1:CMCS=1:4 and OCS1:CMCS=1:8. This is because the aldehyde group of OCS1 reacts completely with the amino group of CMCS when OCS1:CMCS=1:6. Figure 5-6OCS2-CMCS single network self-healing hydrogels with different ratios formed by low-modified OCS2 and CMCS. It can be seen that under the same gelation environment, the elastic modulus reaches 86KPa when OCS2:CMCS=1:6. By comparison, it can be seen that the mechanical properties of the hydrogel formed by high-modified OCS1 are higher than those of the hydrogel formed by low-modified OCS2. This is because in the same mass of OCS, the highly modified OCS1 contains more aldehyde groups, and the formed OCS-CMCS hydrogel has stronger mechanical properties. According to the results, the present invention selected highly modified OCS1 and carried out subsequent experiments under the condition of OCS1:CMCS=1:6.

[0130] 2) Mechanics of double-network OCS-CMCS-TA self-healing hydrogel: In the process of forming OCS-CMCS-TA self-healing hydrogel, the aldehyde group of OCS1 reacts with the amino group of CMCS to form a Schiff base. This strong interaction constitutes the first cross-linked network structure of the hydrogel, but the mechanical properties and adhesion properties of the prepared single-network self-healing hydrogel are relatively weak. For this reason, the present invention solves this problem by introducing TA. Hydrogen bonds are formed between TA and OCS1 and CMCS to form the second cross-linked network structure of the hydrogel, which greatly improves the mechanical and adhesion properties of the hydrogel. The mechanical properties test results of the OCS1-CMCS-TA double-network self-healing hydrogel prepared by immersing the single-network self-healing wet hydrogel with OCS1:CMCS=1:6 in TA solutions of different concentrations are shown in the figure. Figure 7-Figure 8 As shown, by comparison Figure 7-Figure 8 , Figure 3-4 It can be seen that the mechanical properties of the double network self-healing hydrogel formed by soaking in TA solution are as high as 328KPa, which is much higher than 93KPa of the single network self-healing hydrogel. This is because after soaking in TA solution, a large number of hydrogen bonds are formed between TA and OCS1, thereby enhancing the mechanical properties of the hydrogel. And within a certain range, with the increase of the concentration of TA solution, the mechanical properties of the OCS1-CMCS-TA double network self-healing hydrogel first increase and then decrease. When the concentration of TA solution is 3% w / v, the elastic modulus of the OCS1-CMCS-TA double network self-healing hydrogel reaches a maximum value of 328KPa. However, when the concentration of TA solution increases to 10% w / v, the mechanical properties of the OCS1-CMCS-TA double network self-healing hydrogel are reduced to 220KPa. This is because when the concentration of TA is too high, it will react strongly with the surface layer of the hydrogel quickly, forming a harder shell layer, causing TA to penetrate slowly into the gel, resulting in uneven formation of the second cross-linked network of the hydrogel, affecting the mechanical properties of the hydrogel.

[0131] During the experiment, the present invention also used a single network self-healing dry hydrogel with OCS1:CMCS=1:6 to immerse in TA solutions of different concentrations to prepare OCS1-CMCS-TA double network self-healing hydrogel. However, in the subsequent self-healing and adhesion performance tests of the dry hydrogel, the self-healing and adhesion performance were poor, so the wet hydrogel was finally chosen for the experiment. Based on the results, the present invention chose to conduct subsequent experiments with OCS1:CMCS=1:6 and a TA concentration of 3% w / v.

[0132] 3) Network OCS1-CMCS / HAp-TA self-healing hydrogel mechanics: Hydroxyapatite can promote cartilage-bone formation, so hydroxyapatite is widely used in the field of osteochondral tissue engineering scaffold materials. And studies have shown that by adding a series of inorganic new nanoparticles to hydrogels, they can be used as hydrogel mechanical property enhancers. Figure 9-10 The mechanical properties of OCS1-CMCS / HAp-TA self-healing hydrogels with different contents of hydroxyapatite nanoparticles added to the CMCS solution. Figure 9-10 , Figure 7-Figure 8 It can be seen that the elastic modulus of OCS1-CMCS / HAp-TA3 dual network self-healing hydrogel is up to 411 KPa, which is higher than that of OCS1-CMCS-TA3 dual network self-healing hydrogel. Figure 9-10 It can be seen that when the concentration of nano-HAp increases from 2% w / v to 6% w / v, the elastic modulus of the prepared OCS1-CMCS / HAp-TA3 hydrogel continues to rise. When the HAp concentration is 6% w / v, the maximum elastic modulus of the OCS1-CMCS / HAp-TA3 self-healing hydrogel is 411KPa. However, when the concentration of nano-hydroxyapatite solution increases to 10% w / v, the mechanical properties of the OCS1-CMCS / HAp-TA3 self-healing hydrogel are reduced to 318KPa. This is because the addition of excessive HAp causes HAp to be unable to be completely dispersed in the hydrogel, and HAp is unevenly mixed, which in turn causes uneven distribution of Hap nanoparticles in the hydrogel. During the compression process, the hydrogel is subjected to uneven force, making the hydrogel more easily crushed.

[0133] Example 4. Adhesion performance test

[0134] Take a small amount of added OCS1-CMCS-TA hydrogel and fully contact it with the finger, and observe its adhesion behavior by stretching the finger. In order to quantitatively analyze the adhesion strength of OCS1-CMCS-TA hydrogel, a glass slide was used for testing. First, the glass slide was soaked in a 5% gelatin solution for 0.5h, taken out and dried naturally. Then, the hydrogel was sandwiched between two glass slides to make a glass slide / hydrogel / glass slide sandwich structure, such as Fig.11As shown. Then the test was carried out on the mechanical tester at a speed of 5 mm / min. The maximum pulling force F for pulling the two glass slides apart was recorded.

[0135] The formula for calculating adhesion strength is: δ = F / A

[0136] Wherein, A is the overlapping area, F is the maximum tensile stress, and each sample was measured three times in parallel.

[0137] Results: Fig.12 As shown, Fig.12 -A~ Fig.12 -B shows that the hydrogel can adhere to the plastic gloves and can withstand a certain pulling force without falling off. Fig.12 -C~ Fig.12 -E is the hydrogel that adheres to different media, including skin, rubber, and plastic. Therefore, OCS1-CMCS-TA hydrogel has excellent tissue adhesion. This is because the present invention further introduces TA into the OCS-CMCS hydrogel, so that the hydrogel has a large number of catechol groups and pyrogallol groups, so that the hydrogel has a mussel-like adhesion effect and can adhere to the surface of hydrophilic and hydrophobic materials. The excellent tissue adhesion of OCS1-CMCS-TA hydrogel not only supports cell adhesion, proliferation and diffusion, but also maintains the phenotype of chondrocytes, which is of great significance for cartilage repair.

[0138] The results of quantitatively measuring the adhesion strength of OCS-CMCS-TA hydrogel using a mechanical tester are as follows: Figure 13-14 As shown, the adhesion strength of OCS1-CMCS-T0 hydrogel is 1.5KPa, while the adhesion strength of OCS1-CMCS-T1 hydrogel is 5.7KPa. By comparison, it can be seen that the adhesion strength of the hydrogel is improved by soaking in TA solution. The improvement in the adhesion strength of the hydrogel is due to the introduction of TA. TA contains a large number of catechol groups, which causes hydrophobic and hydrogen bond interactions between the substrate and the catechol groups. With the increase of TA concentration, the shear adhesion strength of OCS1-CMCS-TA hydrogel gradually increases, but when the TA content continues to increase, the adhesion strength of OCS-CMCS-TA hydrogel decreases instead, with a strength of 4.5KPa. This is because when the concentration of TA is too high, a harder shell layer will be formed on the surface of the hydrogel, so the uneven formation of the hydrogel affects the adhesion strength of the hydrogel. When OCS1-CMCS / HAp-TA3 hydrogel was prepared by adding hydroxyapatite to carboxymethyl chitosan, the shear adhesion strength test was carried out. The test results are shown in Figure 15-16 As shown, compared with OCS1-CMCS-T3 hydrogel, under the preparation conditions of a certain amount of HAp, the introduction of hydroxyapatite did not significantly change the adhesion strength of the hydrogel.

[0139] Combined with the mechanical and adhesion test results, the present invention prepared a gradient self-healing hydrogel through the self-healing and adhesion between hydrogels. Fig.17 As shown, the preparation conditions of the three layers from top to bottom are: the first layer is OCS1-CMCS-TA1 (OCS1:CMCS=1:6, TA concentration is 1% w / v), the second layer is OCS1-CMCS-TA3 (OCS1:CMCS=1:6, TA concentration is 3% w / v), and the third layer is OCS1-CMCS / HAp-TA3 (OCS1:CMCS=1:6, TA concentration is 3% w / v, HAp concentration is 6% w / v). The elastic moduli of the three layers of hydrogel are 282KPa, 328KPa, and 411KPa, respectively. The adhesion strengths of the three layers of hydrogel are 5.7KPa, 9.3KPa, and 9.1KPa, respectively.

[0140] Example 5. SEM observation

[0141] The morphological characteristics of the hydrogel were observed using SEM. SEM is a method for characterizing the surface morphology of materials, and uses different electron signals formed by the interaction between the electron beam and the sample surface for microscopic imaging. Its working principle is that the high-energy electron beam interacts with the sample surface, obtains characteristic signals, and forms characteristic images through the imaging function of the instrument. In addition, the gradient hydrogel was freeze-dried and cut into three parts, the hydrogel sample was quenched with liquid nitrogen, and then the brittle cross-section was sprayed with gold for 1 minute, and the microscopic pore structure of the three layers of hydrogel was observed separately.

[0142] Results: The morphological characteristics of OCS1-CMCS-TA self-healing hydrogel and OCS1-CMCS / HAp-TA self-healing hydrogel are shown in Fig.18 As shown. The OCS1-CMCS-TA1 self-healing hydrogel exhibits the characteristics of uniform structure, dense structure, and very obvious pore structure. After further increasing the concentration of TA, the pore size of the OCS1-CMCS-TA3 self-healing hydrogel becomes smaller than that of the OCS1-CMCS-TA1 self-healing hydrogel, and the network structure becomes more dense. This is because the increase in TA concentration enhances the hydrogen bonding between TA and OCS1 and CMCS, thereby increasing the cross-linking density of the OCS1-CMCS-TA3 self-healing hydrogel. After the introduction of HAp, the OCS1-CMCS / HAp-TA3 self-healing hydrogel exhibits a uniform structure, a denser network structure, a reduced pore structure, and nano-hydroxyapatite particles can be seen on the pore walls.

[0143] Example 6. Swelling performance test

[0144] Swelling property is an important indicator for evaluating scaffold performance. As a tissue engineering scaffold, its rapid swelling property is conducive to the transport of nutrients, so that cells embedded in the hydrogel will not die due to long-term lack of nutrients. In order to more accurately evaluate the swelling properties of the self-healing hydrogel, this embodiment uses freeze-dried self-healing hydrogel to test the swelling properties. The gradient hydrogel was freeze-dried and cut into three parts, and each layer of hydrogel sample was weighed and measured before being soaked in 37°C PBS buffer. Within a predetermined time, the water-absorbed hydrogel was weighed (1h, 2h, 3h, 4h, 5h, 6h). The mass swelling rate of the hydrogel (W SR ) can be calculated according to the following formula:

[0145] W SR (%)=(m s -m0) / m0×100%

[0146] Among them, m s and m0 is the mass of the hydrogel before and after swelling. Each sample was measured three times in parallel.

[0147] Results: Fig.19 As shown, in the first hour, OCS-CMCS-TA1, OCS-CMCS-TA3 and OCS-CMCS / HAp-TA3 hydrogels rapidly absorbed water. By the fourth hour, the swelling rates of the three hydrogels were 1083%, 1077% and 954%, respectively. Swelling equilibrium was reached. Comparing CS-CMCS-TA1 and OCS-CMCS-TA3 hydrogels, it was found that the swelling rates of the two were not much different, because the concentration of TA solution did not affect the network structure of the hydrogel. At the same time, the swelling rates of CS-CMCS-TA1 and OCS-CMCS-TA3 hydrogels were higher than that of OCS-CMCS / HAp-TA3 hydrogels, because the OCS-CMCS / HAp-TA3 hydrogel network contained Hap nanoparticles, which made the structure of the hydrogel network more compact and it was difficult for water molecules to enter the interior, so the equilibrium mass swelling rate was lower than that of OCS-CMCS-TA1 and OCS-CMCS-TA3 hydrogels.

[0148] Example 7. Self-healing performance test

[0149] In order to study the self-healing properties of the hydrogel, this example uses the shear-healing method to study the self-healing properties of the OCS-CMCS-TA self-healing hydrogel. Two identical self-healing hydrogels were prepared under the same conditions, one of which was dyed red with rhodamine and the other was not dyed. Then the two hydrogels were cut into 4 pieces, and the two hydrogels of different colors were seamlessly placed on the fracture surface. At room temperature without any external pressure, they were allowed to self-heal, and their microscopic healing was observed under a microscope. After a certain period of time, the healed hydrogel was horizontally stretched with tweezers to observe the healing condition.

[0150] The results are as follows Fig. 20 As shown, Fig. 20 -A, two pieces of OCS-CMCS-TA hydrogels of different colors are cut into four pieces, and the hydrogels of different colors are spliced ​​together. It can be seen that the hydrogel formed by Schiff base bonds and hydrogen bonds cross-linking of the present invention has super strong self-healing properties. The gaps in the hydrogel have disappeared after 1 hour, and the hydrogel has completely self-healed after 3 hours. Fig. 20 -B shows that after 5 hours, the entire hydrogel turns red. At the same time, the hydrogel that has self-healed for 5 hours is stretched, and it can be seen that the self-healing gaps are completely invisible and the color is uniform. It cannot be pulled apart by applying force with tweezers. The results show that the hydrogel has a good self-healing effect.

[0151] Example 8. Antioxidant performance test

[0152] In this embodiment, the antioxidant capacity of OCS1-CMCS-TA hydrogel and OCS1-CMCS / HAp-TA hydrogel was tested by the ability to remove DPPH. DPPH has an absorption peak at 517nm. The ethanol solution of DPPH is purple. When the hydrogen atoms in OCS1-CMCS-TA hydrogel and OCS1-CMCS / HAp-TA hydrogel are paired with electrons, reduced DPPH is generated, and the absorption rate is reduced, making the color of the solution light yellow. The more electrons are removed, the stronger the antioxidant capacity. Simple OCS1-CMCS hydrogel does not have the ability to remove DPPH free radicals. Each layer was prepared according to the three-layer preparation conditions of the gradient self-healing hydrogel, and the antioxidant test was performed. The specific experimental steps are: weigh 100 mg of wet hydrogel and soak it in 6 mL of 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) solution with a concentration of 80 μg / mL to allow the hydrogel to fully react with the solution. The absorbance of the solution at 517 nm was measured by a UV spectrophotometer. The DPPH free radical scavenging rate can be calculated according to the following formula:

[0153] Free radical scavenging rate = (D0-D i ) / D0×100%

[0154] Among them, D0 is the absorbance of the blank group, D i is the absorbance of the experimental group. Each sample was measured in parallel 3 times.

[0155] The results are as follows Figure 21-22 As shown in the figure, after the introduction of TA, TA contains abundant phenolic hydroxyl groups, which can be used as a terminator of hydroxyl radicals to reduce DPPH to diphenylhydrazine. The DPPH scavenging rate of OCS-CMCS-TA1 hydrogel sample is 68%. With the increase of TA content, the content of catechol and pyrogallol increases, and the scavenging ability of DPPH free radicals is enhanced. The DPPH scavenging rate of OCS-CMCS-TA3 hydrogel sample reaches 81%, and the DPPH scavenging rate of OCS-CMCS / HAp-TA3 hydrogel sample reaches 80%. Oxygen free radicals (reactive oxygen species, ROS) are the direct cause of osteoarthritis chondrocyte damage, aging and apoptosis. TA has good antioxidant capacity and plays an important role in maintaining the oxidative balance of cells. Therefore, maintaining a stable level of ROS in cells is a feasible solution for the treatment of osteoarthritis.

[0156] Through the experimental results of the above-mentioned embodiments 2 to 8, the following conclusions can be drawn:

[0157] (1) Single-network self-healing hydrogels were prepared based on the Schiff base reaction between OCS and CMCS. The mechanical properties of the hydrogels increased with the increase of the OCS modification degree and the volume ratio of OCS / CMCS. The results showed that when the OCS aldehyde modification degree was 1.2 mmol / g and OCS:CMCS=1:6, the elastic modulus was 93 kPa.

[0158] (2) In order to enhance the mechanical properties of the hydrogel and give the hydrogel tissue adhesion and antioxidant properties, TA was introduced into the system. The optimal preparation conditions of the OCS1-CMCS-TA double network self-healing hydrogel are (OCS1:CMCS=1:6, TA3%), with the highest elastic modulus of 328KPa and the adhesion strength of 9.3KPa.

[0159] (3) The introduction of HAp not only enhances the mechanical properties of the hydrogel, but also helps bone formation. The optimal preparation conditions of OCS1-CMCS / HAp-TA3 dual network self-healing hydrogel are (OCS1:CMCS=1:6, TA concentration is 3% w / v, HAp concentration is 6% w / v), and its highest elastic modulus is 411 KPa.

[0160] (4) Based on the good self-healing and adhesion properties of hydrogels, a three-layer gradient self-healing hydrogel was prepared, and the bonding interface between the layers was firm. The gradient self-healing hydrogel has good mechanical properties, tissue adhesion, self-healing, swelling and good antioxidant properties.

[0161] In summary, it can be concluded that the optimal preparation conditions for the three-layer gradient self-healing hydrogel are: the first layer: OCS1-CMCS-TA1 hydrogel, OCS1:CMCS = 1:6, TA concentration of 1% w / v, OCS1 concentration of 20% w / v, CMCS concentration of 4% w / v; the second layer is OCS1-CMCS-TA3 hydrogel, OCS1:CMCS = 1:6, TA concentration of 3% w / v, OCS1 concentration of 20% w / v, CMCS concentration of 4% w / v; the third layer is OCS1-CMCS / HAp-TA3 hydrogel, OCS1:CMCS = 1:6, TA concentration of 3% w / v, HAp concentration of 6% w / v, OCS1 concentration of 20% w / v, CMCS concentration of 4% w / v. The gradient self-healing hydrogel prepared under these conditions has good mechanical properties, tissue adhesion properties and antioxidant properties, and has the potential to be used in cartilage-bone integrated repair.

Claims

1. A composition for preparing a three-layer gradient self-healing hydrogel, characterized in that: The composition comprises composition A, composition B and / or composition C; the composition A comprises modified chondroitin sulfate, carboxymethyl chitosan and tannic acid, the concentration of tannic acid in the composition A is 0.5% w / v-1.5% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:5-1:7; the composition B comprises modified chondroitin sulfate, carboxymethyl chitosan and tannic acid, the concentration of tannic acid in the composition B is 2.5% w / v-3.5% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:5-1:7; the composition C comprises modified chondroitin sulfate, carboxymethyl chitosan, tannic acid and nano-hydroxyapatite, the concentration of tannic acid in the composition C is 2.5% w / v-3.5% w / v, and the volume ratio of modified chondroitin sulfate to carboxymethyl chitosan is 1:5-1:

7.

2. The composition according to claim 1, characterized in that In the composition A, the composition B and the composition C, the concentration of modified chondroitin sulfate is 18% w / v to 22% w / v; in the composition A, the composition B and the composition C, the concentration of carboxymethyl chitosan is 3% w / v to 5% w / v; and in the composition C, the concentration of nano-hydroxyapatite is 5% w / v to 7% w / v.

3. The composition according to claim 1, characterized in that The modified chondroitin sulfate is aldehyde-modified chondroitin sulfate, wherein the aldehyde content is 1.0 mmol / g to 1.5 mmol / g.

4. The composition according to claim 1, characterized in that The tannic acid concentration in the composition A is 1% w / v, and the volume ratio of the modified chondroitin sulfate to the carboxymethyl chitosan is 1:6; the tannic acid concentration in the composition B is 3% w / v, and the volume ratio of the modified chondroitin sulfate to the carboxymethyl chitosan is 1:6; the tannic acid concentration in the composition C is 3%, and the volume ratio of the modified chondroitin sulfate to the carboxymethyl chitosan is 1:6; the modified chondroitin sulfate is aldehyde-modified chondroitin sulfate with a concentration of 20% w / v, wherein the aldehyde content is 1.2 mmol / g; the concentration of the carboxymethyl chitosan is 4% w / v; and the concentration of the nano-hydroxyapatite is 6% w / v.

5. The method for preparing the three-layer gradient self-healing hydrogel according to claim 1, characterized in that: The steps include: (1) Preparation of OCS1-CMCS-TA1 hydrogel: a modified chondroitin sulfate solution and a carboxymethyl chitosan solution are mixed to prepare a chondroitin sulfate / chitosan self-healing hydrogel through a dynamic Schiff base reaction; the chondroitin sulfate / chitosan self-healing hydrogel is immersed in a tannic acid solution with a concentration of 0.5% w / v to 1.5% w / v to obtain the OCS1-CMCS-TA1 hydrogel; (2) Preparation of OCS1-CMCS-TA3 hydrogel: a modified chondroitin sulfate solution and a carboxymethyl chitosan solution were mixed to prepare a chondroitin sulfate / chitosan self-healing hydrogel through a dynamic Schiff base reaction; the chondroitin sulfate / chitosan self-healing hydrogel was immersed in a tannic acid solution with a concentration of 2.5% w / v to 3.5% w / v to obtain the OCS1-CMCS-TA3 hydrogel; (3) Preparation of OCS1-CMCS / HAp6-TA3 hydrogel: adding nanohydroxyapatite to a carboxymethyl chitosan solution to obtain a CMCS / HAp solution; mixing the CMCS / HAp solution with a modified chondroitin sulfate solution to obtain an OCS1-CMCS / HAp6 hydrogel; soaking the OCS1-CMCS / HAp6 hydrogel in a tannic acid solution with a concentration of 2.5% w / v to 3.5% w / v to obtain the OCS1-CMCS / HAp6-TA3 hydrogel; (4) Preparation of three-layer gradient self-healing hydrogel: stack the OCS1-CMCS-TA1 hydrogel obtained in step (1), the OCS1-CMCS-TA3 hydrogel obtained in step (2), and the OCS1-CMCS / HAp6-TA3 hydrogel obtained in step (3) in sequence from top to bottom to obtain the three-layer gradient self-healing hydrogel.

6. The preparation method according to claim 5, characterized in that: In step (1), the concentration of the tannic acid solution is 1% w / v; in steps (2) and (3), the concentration of the tannic acid solution is 3% w / v.

7. The preparation method according to claim 5, characterized in that: The modified chondroitin sulfate has an aldehyde content of 1.0 mmol / g to 1.5 mmol / g. The modified chondroitin sulfate is prepared by the following method: after dissolving chondroitin sodium sulfate, sodium periodate is added to carry out an oxidation reaction; after the reaction is completed, an ethanol solution is added and stirred, and the obtained product is precipitated, dialyzed, and freeze-dried to obtain aldehyde-modified chondroitin sulfate.

8. A three-layer gradient self-healing hydrogel prepared by the preparation method according to any one of claims 5 to 7.

9. The three-layer gradient self-healing hydrogel according to claim 8, characterized in that: The OCS1-CMCS-TA1 hydrogel, OCS1-CMCS-TA3 hydrogel and OCS1-CMCS / HAp6-TA3 hydrogel in the three-layer gradient self-healing hydrogel all have a double network structure, wherein the aldehyde group of the modified chondroitin sulfate reacts with the amino group of the carboxymethyl chitosan to form a Schiff base, which constitutes the first cross-linked network structure of the hydrogel; the hydrogen bonds of tannic acid itself, and the hydrogen bonds formed between tannic acid, the modified chondroitin sulfate and the carboxymethyl chitosan, constitute the second cross-linked network structure of the hydrogel.

10. Use of the composition according to any one of claims 1 to 4 and / or the three-layer gradient self-healing hydrogel according to any one of claims 8 to 9 in the preparation of an integrated articular cartilage-bone tissue repair product.

Citation Information

Patent Citations

  • Photo-crosslinking multilayer gradient hydrogel capable of controllably releasing active factors and preparation method of hydrogel

    CN103721293A

  • Bi-phase bone cartilage repairing support and preparing method thereof

    CN105749342A

  • Preparation method of polysaccharide-based hydrogel crosslinked by dynamic imine linkages

    CN107964105A

  • Biomimetic articular cartilage composite hydrogel with gradient stiffness and preparation method thereof

    CN109010921A

  • HAp-CSA-SF composite gel material, and preparation method and application thereof

    CN110787323A